Peran Polresta Manado Dalam Penegakan Hukum Tindak Pidana Pencurian : (Studi di Polresta Manado) - Tengku Said Hafiz; Supriyadi (MLJ Merdeka Law Journal, 2024)
Theft remains prevalent in North Sulawesi, including the jurisdiction of Polresta Manado. This study examines the role of Polresta Manado in law enforcement against theft, the inhibiting factors, and the efforts undertaken. The research method used is empirical legal research. The findings indicate that Polresta Manado functions as a state instrument in maintaining security, enforcing the law, and providing protection to the community. Law enforcement is carried out preventively through patrols, intelligence development, and Binmas, as well as persuasively to encourage public compliance with existing norms. The inhibiting factors include a lack of human resources, the absence of witnesses or CCTV, uncooperative victims, and the expansion of criminal networks. Efforts to overcome these obstacles involve improving human resource capabilities, training, equipment procurement, and optimizing police performance. In summary, Polresta Manado plays a crucial role in law enforcement against theft but faces various challenges that require enhanced resources and community cooperation.  Keywords: Role, Law Enforcement, Theft